2020
DOI: 10.5271/sjweh.3892
|View full text |Cite
|
Sign up to set email alerts
|

Night work, mortality, and the link to occupational group and sex

Abstract: The present study of 42 731 twins showed a significant hazard ratio for "ever" exposure to night work [HR 1.07 (95% CI 1.00-1.15)] and particularly for >5 years of exposure The increased mortality was seen in both white-and blue-collar workers exposed for >5 years, and particularly in male blue-collar workers. Heredity did not influence the results significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Li et al (7) included five cohort studies [of which two were also included in the study by Vyas et al (5)] in a meta-analysis and observed a slightly increased stroke mortality. In a prospective cohort study of Swedish twins, the risk of mortality due to cardiovascular disease (including stroke) was increased among night shift workers, compared to those with no night work, after adjustment for several important risk factors (such as smoking, alcohol consumption, body mass index and physical activity at leisure time) and with higher risk estimates in night workers with a work duration of >5 years (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al (7) included five cohort studies [of which two were also included in the study by Vyas et al (5)] in a meta-analysis and observed a slightly increased stroke mortality. In a prospective cohort study of Swedish twins, the risk of mortality due to cardiovascular disease (including stroke) was increased among night shift workers, compared to those with no night work, after adjustment for several important risk factors (such as smoking, alcohol consumption, body mass index and physical activity at leisure time) and with higher risk estimates in night workers with a work duration of >5 years (10).…”
Section: Discussionmentioning
confidence: 99%
“…Night and shift work have also been found to be associated with poorer lifestyle behaviors and with risk factors of CeVD, such as hypertension and diabetes (17,18), which may influence the risk. In a recent study of Swedish twins, a higher prevalence of overweight and smoking was observed among individuals who had been exposed to night shift work compared to those with no history of night work, but with no obvious difference in the prevalence of alcohol consumption or leisure-time activity (10).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In 2015, 16% of European workers worked more than 48 h per week and 19% worked nights [ 1 ]. These atypical work types have negative impacts on health such as on cardiovascular disease [ 2 ], metabolic disturbance [ 3 , 4 ], mortality [ 5 , 6 ], and depression [ 7 ]. However, although the effects of long working hours (LW) and night work (NW) have been investigated, few have addressed the synergistic effect of LW and NW using national-scale data.…”
Section: Introductionmentioning
confidence: 99%